Response of the Green Alga Chlorococcum humicola Developed in Chu-13 Culture Medium to Different Concentrations of CO2 - Ibrahim M.A Alsal (Journal of Global Pharma Technology, 2016)
Microalgae response is one of the criteria that is adopted in estimating the efficacy of any species or genus in tolerance or the fixation and withdrawal of the influential concentrations of CO2 either in its natural or supplied or combined forms with other gases. For the purpose of the application, the current study was chosen Chlorococcum humicola alga belonging to the green algae to follow the effect of different concentrations of CO2 supplier were (25, 50, 75, 100%) volume/volume, of culture volume in curves, growth rates, times of multiplication, biomass and some fatty acids. The experiment and development of alga in the Chu-13 culture medium was carried out under controlled environmental conditions of temperature and density of light and pH, as they were in the order of (25 ±2, 3000 lux, 7.6) and with a lighting system of 16:8 hour light to darkness. The alga cells was incurred into mentioned concentrations for one time by injection of the algal culture by CO2 using a device (gas-flow-meter) for three repeaters of each concentration. The results were recorded at time of Zero and daily for 18 days. The results showed that the growth curve based on the absorbency values at the wavelength 650 nm recorded from the fourth day a higher value than the standard sample of all the concentrations. The highest values of 0.71 with the concentration (50%).As for the time of multiplication, the study found that a slight differences between the standard sample and all concentrations and recorded the highest value (1.84) in the control sample for the 18th day. The dry biomass at harvest in the end of the experiment, the values were recorded (370, 360, 410, 340) mg dry weight/L at the concentrations (25, 50, 75, 100%) volume/volume respectively, while the control recorded 310 mg/dry weight/ L. The HPLC technique that has been applied to diagnose some fatty acids has also indicated the presence of acids: (Arachidic C20:4, LinoleicC18: 2(Omega6), Oleic C18:1(Omega 9), Plamitolic C16:1, Palmetic C16:0, Myristic C14:0). The highest value (403.93) % was recorded for the palmetic acid with a 100% concentration of CO2 supplier and a lower value of (82.38) % for arachidic acid with a 25% concentration of CO2 compared with the standard sample.  The conclusion of the study that the treatment with CO2 although it has not given growth rates and times is remarkably multiplied but on the other side it gave an increase in the biomass ranged of (19.35, 16.13, 32.25, 9.67%) for CO2 concentrations (25, 50, 75, 100%) volume/volume respectively. As well as identified fatty acids stimulated the increase of total percentage after harvest on day 18th of the treatment with values:  (32.443, 47.820, 53.443, 121.211, 144.409, 262.636) for each (Palmetic, Pamiotolic, Myristic  Oleic, Linoleic, Arachidic) respectively.Keywords: Microalgae, CO2, Biofixation, Capturing of CO2, Chlorococcum humicola alga.